Some New Formulae for Genocchi Numbers and Polynomials Involving Bernoulli and Euler Polynomials - Serkan Araci; Mehmet Acikgoz; Erdoğan Şen (International Journal of Mathematics and Mathematical Sciences)
We give some new formulae for product of two Genocchi polynomials including Euler polynomials and Bernoulli polynomials. Moreover, we derive some applications for Genocchi polynomials to study a matrix formulation.